2009
DOI: 10.1007/s11230-009-9178-6
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Testudotaenia testudo (Magath, 1924) (Eucestoda: Proteocephalidea), a parasite of Apalone spinifera (Le Sueur) (Reptilia: Trionychidae) and Amia calva L. (Pisces: Amiidae) in North America and erection of the Testudotaeniinae n. subfam.

Abstract: Testudotaenia testudo (Magath, 1924) is redescribed from the intestine of the softshell turtle Apalone spinifera (Le Sueur) (Trionychidae) and the bowfin Amia calva Linnaeus (Amiidae) from Reelfoot Lake, Tennessee, United States. A new subfamily, the Testudotaeniinae, is erected. The new taxon differs from all proteocephalidean subfamilies in the position of the genital organs in relation to the longitudinal internal musculature, i.e. the testes are cortical, rarely medullary; the ovary is partly medullary, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…This was true for multiple genera in both the Proteocephalidae (e.g., Scholz et al, 1999; de Chambrier, 2006; de Chambrier and de Chambrier, 2010; Ash et al, 2012; Rambeloson et al, 2012) and the Monticelliidae (e.g., Gil de Pertierra, 2002; Gil de Pertierra, 2005; de Chambrier et al, 2006; Scholz et al, 2008; Arredondo et al, 2013; Gil de Pertierra and de Chambrier, 2013). While promising, this feature requires more detailed study across genera in both families as SEM data are available only for more recently described taxa and a few exceptions may exist (e.g., possibly de Chambrier et al, 2009; Gil de Pertierra, 2009). Also worth noting is the fact that Acanthobothrium and Uncibilocularis species bear a dense covering of gladiate spinitriches restricted to the cephalic peduncle (sensu Caira et al, 1999), a region of the body immediately posterior to the scolex proper that may be homologous to the neck and/or proliferation zone.…”
Section: Discussionmentioning
confidence: 99%
“…This was true for multiple genera in both the Proteocephalidae (e.g., Scholz et al, 1999; de Chambrier, 2006; de Chambrier and de Chambrier, 2010; Ash et al, 2012; Rambeloson et al, 2012) and the Monticelliidae (e.g., Gil de Pertierra, 2002; Gil de Pertierra, 2005; de Chambrier et al, 2006; Scholz et al, 2008; Arredondo et al, 2013; Gil de Pertierra and de Chambrier, 2013). While promising, this feature requires more detailed study across genera in both families as SEM data are available only for more recently described taxa and a few exceptions may exist (e.g., possibly de Chambrier et al, 2009; Gil de Pertierra, 2009). Also worth noting is the fact that Acanthobothrium and Uncibilocularis species bear a dense covering of gladiate spinitriches restricted to the cephalic peduncle (sensu Caira et al, 1999), a region of the body immediately posterior to the scolex proper that may be homologous to the neck and/or proliferation zone.…”
Section: Discussionmentioning
confidence: 99%
“…A few parasites from amphibians and turtles, as well as Proteocephalus perplexus La Rue, 1911 from bowfin ( Amia calva L., 1766), also belong to this large polytomy. de Chambrier et al (2009a) showed that Testudotaenia Freze, 1965 of the monotypic subfamily Testudotaeniinae was part of a North American clade of proteocephalid parasites of fishes despite its distinctive morphology. These results do not contradict this hypothesis although Testudotaenia ’s closest relatives cannot be inferred from the present tree.…”
Section: Discussionmentioning
confidence: 99%
“…At the morphological level, the difficulty of defining reliable informative characters has prevented the construction of a stable taxonomic arrangement of the group (Rego 1994, 1995). The traditionally accepted families Proteocephalidae and Monticelliidae have been abandoned, and the whole group has been split into a number of subfamilies and genera, including the type genus Proteocephalus Weinland, 1858, which are sometimes obviously artificial because of their lack of synapomorphies and diversity of life-history traits (see de Chambrier et al 2004c, 2009a). Molecular studies that have tried to resolve the proteocephalidean tree topology have largely been based on the variable domains (D1–D3) of the large nuclear ribosomal RNA subunit (28S rDNA), using increasingly larger datasets, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Onchoproteocephalidean tapeworms, with a cosmopolitan distribution, represent a diverse group of parasites with 316 valid species in bony fish, lizard, snake and amphibian hosts (Caira et al , 2017), and 246 valid species in elasmobranch hosts (Caira et al , 2017). The traditionally accepted families Proteocephalidae and Monticelliidae have been abandoned, and the only family Protecephalidae has been split into a number of subfamilies and genera (de Chambrier et al ., 2009). 28S rDNA-based phylogeny suggests that most of the presently recognized subfamilies (and genera) appear to be non-monophyletic, and a deep systematic reorganization of the order is thus needed (de Chambrier et al , 2015).…”
Section: Introductionmentioning
confidence: 99%